SISTEM INFORMASI COVID-19 KOTA BATAM DAN SKRINING MANDIRI MENGGUNAKAN METODE FORDWARD CHAINING - syaeful Aklani; Jimmy Chandra (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2021)
The development of the covid-19 virus in Indonesia, according to reports from the Batam city health office, has increased the patient graph and to see someone affected by Covid-19 or unable to screen an independent application, one of them is with a 19 in the city of Batam because on the lawancorona.batam.go.id site it is still manual and has no information system yet, with the covid-19 recap system and independent screening it is hoped that it can help the people of Batam, especially to be more careful in carrying out their daily activities , the purpose of this research is to provide information related to information related to Covid 19, and to check whether someone has the Covid-19 virus symptoms or not through early detection, one of which is by doing independent screening through this application.